Technical efficiency and its determinants in the Spanish construction sector pre- and post-financial crisis - Kapelko, Magdalena; Oude Lansink, Alfons (International Journal of Strategic Property Management, 2015)
This paper estimates technical efficiency in the Spanish construction sector before and after the start of the current financial crisis, and examines the impact of socio-economic factors on technical efficiency. Bias-corrected efficiency measures are obtained using Data Envelopment Analysis with bootstrap for a sample of medium-sized and large construction firms over the period 2000–2010. Next, bias-corrected efficiency scores are regressed on the variables explaining efficiency using bootstrap truncated regression. The results show that technical efficiency is very low and is significantly lower after the beginning of the financial crisis than before. Firms with the highest technical efficiency scores have the lowest input-ratio for material and employee costs to output and the highest for fixed assets. The examination of the determinants of technical efficiency indicates that efficiency is higher for firms that export, are highly leveraged, are integrated in the form of joint stock company, and are located in Spanish regions with higher GDP per capita, while firms with high stock relatively to turnover have lower technical efficiency. Technical efficiency increases with size for relatively small sized construction firms, but decreases beyond a critical firm size, while technical efficiency decreases with age for young firms, but eventually increases for older firms. First Publish Online: 1 Apr 2015